Hadith #3270 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abdur Rahman bin Abi Bakr; Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Salm bin Nwh bin Aby سالم بن نوح بن أبي (Sunan Abi Dawud)
Some guests visited us, and Abu Bakr was conversing with the Messenger of Allah (ﷺ) at night. He (Abu Bakr) said: I will not return to you until you are free from their entertainment and serving them food. So he brought them food, but they said: We shall not eat it until Abu Bakr comes (back). Abu Bakr then came and asked: What did your guest do? Are you free from their entertainment ? They said: No. I said: I brought them food, but they refused and said: We swear by Allah, we shall not take i
Grade: Sahih

Hadith #5039 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Salm bin Nwh bin Aby سالم بن نوح بن أبي; Umar bin Jabir al-Yemami عمر بن جابر اليمامي (Sunan Abi Dawud)
Two men sneezed in the presence of the prophet (May peace be upon him). He said : Allah have mercy on you! To one and not to the other. He was asked: Messenger of Allah! Two persons sneezed. Ahmad’s version has: You invoked a blessing on one of them and left the other. He replied : This man praised Allah, and this man did not praise Allah.
Grade: Sahih